2021
DOI: 10.1101/2021.11.20.21266640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient experience with healthcare: Feedback for a ‘Post COVID-19 clinic’ at a tertiary care center in rural area

Abstract: PurposePost-acute sequelae of SARS-CoV-2 (PASC) is a complex condition with multisystem involvement. We assessed patients’ perspectives and experience with a PASC clinic established at University of Iowa in June 2020.MethodsWe conducted a mixed-method survey in June 2021 to ask PASC clinic patients about 1) PASC symptoms and their impact on physical and mental health, and cognition using the PROMIS Global Health and Cognitive Function abilities items, and 2) satisfaction with clinic services and referrals, bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The Centers for Disease Control and Prevention (CDC) defines post-COVID-19 conditions as “new, returning, or ongoing health problems people can experience after first being infected with the virus that causes COVID-19” [ 4 ]. Studies on long COVID have reported multisystem involvement with a range of physical and neuropsychiatric symptoms after infection [ 5 , 6 , 7 , 8 , 9 , 10 ]. Shortness of breath, cough, chest pain, dizziness, fatigue, anosmia, dysgeusia, headache, and cognitive difficulties are among the most common symptoms reported in the studies [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Centers for Disease Control and Prevention (CDC) defines post-COVID-19 conditions as “new, returning, or ongoing health problems people can experience after first being infected with the virus that causes COVID-19” [ 4 ]. Studies on long COVID have reported multisystem involvement with a range of physical and neuropsychiatric symptoms after infection [ 5 , 6 , 7 , 8 , 9 , 10 ]. Shortness of breath, cough, chest pain, dizziness, fatigue, anosmia, dysgeusia, headache, and cognitive difficulties are among the most common symptoms reported in the studies [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early qualitative research on the broader patient experience of COVID-19 has revealed some common themes including symptom variability, a heavy sense of stigma, siloed care, the burden on patients to access care, and fear of a permanent reduction in physical and cognitive abilities [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Open-ended survey studies have also highlighted themes such as multiple symptoms with variable intensity, challenges seeking medical care, motivation to move forward with self-compassion, and also interest in participating in research to explore more about the condition [ 10 , 28 , 29 ]. A recent meta-analysis of 81 studies reported 32% of patients experienced fatigue and 22% reported cognitive impairment 12 or more weeks after COVID-19 diagnosis [ 30 ].…”
Section: Introductionmentioning
confidence: 99%